2022
DOI: 10.1016/j.ijnurstu.2021.104121
|View full text |Cite
|
Sign up to set email alerts
|

Delegation of medication administration from registered nurses to non-registered support workers in community care settings: A systematic review with critical interpretive synthesis

Abstract: Introduction Healthcare workforces are currently facing multiple challenges, including aging populations; increasing prevalence of long-term conditions; and shortfall of registered nurses. Employing non-registered support workers is common across many countries to expand service capacity of nursing teams. One task delegated to non-registered support workers is medication administration, which is considered a complex task, with associated risks. This is an important topic given the predicted global… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 57 publications
(87 reference statements)
1
16
0
Order By: Relevance
“…In line with delegation of medicines administration internationally (Shore et al, 2021), insulin delegation was primarily driven by increased service demand, and the principal benefits related to increased service capacity. However, a surprising range of additional benefits were reported for patients, healthcare support workers, the community nursing teams and service provision.…”
Section: Benefits Of the Delegation Of Insulin Administrationmentioning
confidence: 99%
See 3 more Smart Citations
“…In line with delegation of medicines administration internationally (Shore et al, 2021), insulin delegation was primarily driven by increased service demand, and the principal benefits related to increased service capacity. However, a surprising range of additional benefits were reported for patients, healthcare support workers, the community nursing teams and service provision.…”
Section: Benefits Of the Delegation Of Insulin Administrationmentioning
confidence: 99%
“…Previous research has shown delegation to be influenced by inter‐professional and team relationships (Campbell et al, 2020; Hopkins et al, 2012), the clarity of roles and responsibilities (Blay & Roche, 2020; Munn et al, 2013) and the quality of supervision (Bifarin & Stonehouse, 2017). While benefits of delegation have been identified for services, patients and staff, concerns have also been raised by registered healthcare workers about staff acceptance, role blurring and patient safety (Shore et al, 2021). It has been reported that some registered nurses view the employment of healthcare support workers as a cheap replacement for Nurses (Alcorn & Topping, 2009; Thornley, 2000).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…As a result, COVID-19 rapidly spread in care settings, leading to a significant rise in deaths and excess mortality, especially in care homes [4]. Meanwhile, the Government's response was perceived as slow and indecisive [5], managers had to keep up with continuously changing guidance [6], and care workers had to take on tasks usually undertaken by registered nurses [7,8]. The increased volume of tasks during the pandemic resulted in higher workloads among existing staff [9].…”
Section: Introductionmentioning
confidence: 99%